Judicial process in America - Carp, Robert A., 1943-; Stidham, Ronald, 1940-; Manning, Kenneth L. (Kenneth Luis) (Washington, D.C. : CQ Press, 2011)
The eighth edition of Judicial Process in America gives a thorough overview of the American judiciary at every level, paying particular attention to the link between the courts, public policy, and the political environment. In addition to comprehensive updates on such topics as the role of the courts in the war on terror, affirmative action, and business regulation, notable additions to this eighth edition include discussion of: the probable impact that President Obama will have on the composition of the federal judiciary and on subsequent judicial "output; the highly conservative impact that former President Bush had on the federal judiciary; Justice Sonia Sotomayor's appointment, as well as Chief Justice John Roberts's leadership on the Supreme Court; the role the courts are playing in the policy realm of same-gender marriages and discrimination based on sexual orientation; and more comparative references and examples throughout the book. Adopters and students alike will also appreciate the new Web sites that the authors added to the end-of-chapter suggested resources, as well as the unique annotated U.S. Constitution found in the appendix. This extensive revision of a classic text brings new life to a standard-bearer for judicial process classes. - Publisher.
Foundations of law in the United States -- The federal judicial system -- State judicial systems -- Jurisdiction and policymaking boundaries -- State judges -- Federal judges -- Policy links between the citizenry, the president, and the federal judiciary -- Lawyers, litigants, and interest groups in the judicial process -- Crime and procedures prior to a criminal trial -- The criminal trial and its aftermath -- The civil court process -- Decision making by trial court judges -- Decision making in collegial courts -- Implementation and impact of judicial policies -- Policymaking by American judges : a synthesis.
Includes bibliographical references and indexes.
1 2
Keywords: Justice, Administration of -- United States; Courts -- United States; Judicial process -- United States